Perbandingan Hasil Tes Speed Dilihat Dari Urutan Item Tes Berdasarkan Sumber Energi - Mutaqim, Imam; Imanudin, Iman; Umaran, Unun; Subarjah, Herman (Universitas Hamzanwadi, 2024)
The purpose of this study was to examine the comparison of speed test results seen from the order of test items based on energy sources and those that are not. The method of this research is an experimental method, using a one group pretest-posttest design. The population in this study were all Sports Science students who were contracting the Test and Measurement course, 33 sports science students participated in this study selected using purposive sampling technique. Each sample performs tests and physical condition measurements with a sequence of test items based on energy sources and those that are not. The research instrument used in carrying out data collection from this study is a pattern of test item arrangement. The results of the speed test with the order of test items and measurements based on energy sources and those that do not have a difference in the average value of 0.15242 points. With the results of statistical analysis using IBM SPSS Statistics 23 software, it is known that the Sig, (2-tailed) value is 0.000 < 0.05. The average pretest with a value of 3.7139 and a standard deviation of 0.52093. While the average posttest result is 3.8664 with a standard deviation of 0.55640. So it can be concluded that there is a significant difference between the results of the speed test whose test item order is based on energy sources and those that are not.